Makna Ungkapan “Jangan Kamu Membangkitkan Dan Menggerakkan Cinta Sebelum Diingininya (Kidung Agung 2:7b)” Dan Implementasinya Bagi Pasangan Pranikah - Intan Falensia Sambeta; I Gede Agus Z.P.; Riko Arnawijaya, Ray (JURNAL ILUMINASI, 2024)
This paper explores the meaning of the phrase  "Do not arouse or awaken love until it so desires." in Song of Solomon 2:7b and its implications for premarital couples. This phrase emphasises the importance of self-control in love and desire, especially before marriage. Using qualitative methods and theological interpretation, this study explores the theological meaning of the verse and its relevance in the modern context. The results show that self-control in love, in accordance with biblical teaching, is essential to maintaining the sanctity of premarital relationships. The modern phenomenon shows that many young couples are failing to maintain this boundary, which has the potential to undermine marriage preparation and have long-term negative consequences. Therefore, applying the principles of love contained in the Song of Songs can help young couples build a strong and God-blessed marriage foundation. This study also aims to provide practical guidance for pre-marital couples in maintaining the sanctity of love and delaying physical relations until the right time according to God's will, in order to avoid temptation and build a healthy and balanced relationship.